Leucena versus coconut meal as supplement for grazing lactating cows - Filho, Orlando Monteiro de Carvalho; Languidey, Pablo Hoentsch; Costa, João Albani (Pesquisa Agropecuaria Brasileira, 2014)
Nine of twelve lactating Holstein x Zebu cows grazing a Brachiaria plantaginea - Cenchrus ciliaris pasture were supplemented with 1.5 kg of coconut meal (group B), 4.8 kg of fresh Leucaena leucocephala (group C), and 0.75 kg of coconut meal + 2.4 kg of fresh leucena per cow/day (group D). The three remaining cows were given no supplement (group A). Effect of these treatments on milk yield were evaluated in a 4 x 4 latinsquare experimental design, with 14-day experimental periods. Forage availability (DM/ha) was over 1,782 kg. The milk yield of unsupplemented cows averaged 7.8 kg/cow/day, significantly lower than those of supplemented cows. The highest milk yield (P < 0.05) was observed in B cows (9.0 kg/cow/day). Cows on group C averaged 8.4 kg, which was shown to be the most profitable treatment under local marketing conditions. Cows on group D (8.3 kg/day) did not differ (P < 0.05) from those on group C, showing no benefit from the partial replacement of coconut meal.